WASTAGE IN PRIMARY EDUCATION: IT’S EFFECT ON SOCIO-EDUCATIONAL STATUS OF SOKOTO STATE - Umar, Shehu; Muhammad, Abubakar Kabir; Abdullahi, Aisha (Sokoto Educational Review, 2017)
Wastage in education cuts across all levels of instruction, primary, secondary and high education. This paper examined the concept of wastage in the field of primary education. How such wastage affects the social and educational status of Sokoto State. The causes of wastage were highlighted and the constraints emanating from socio-social, religious and governmental were examined and recommendations offered. All stakeholders in primary education have to join hands together to control wastage in this vital sub-sector.